Utilisation of CRM and its impact on sales performance: a study of sales professionals working in a virtual environment. (1st January 2011) - Rodriguez, Michael; Yim, Frederick
With the advancement in communication technologies in the last decade firms have implemented technology initiatives that enable sales professionals to have access to customer data and enable them to increase workplace efficiency by communicating electronically with their clients and colleagues. Many sales professionals work remotely outside the traditional office and technology, in the form of customer relationship marketing (CRM), allows sales professionals to devote more flexible time to better serve their customers. By utilising CRM technology, today's sales professionals can communicate and collaborate with clients and managers anytime, anywhere. Findings of this study support the hypotheses that CRM utilisation has positive impacts on sales performance, namely sales process effectiveness, performance with customers, and administrative efficiency. Among the three performance measures, CRM usage has the greatest impact on sales process effectiveness. The study also supports that when sales professionals work in a virtual environment they are more likely to utilise CRM.